2017
DOI: 10.1049/iet-sen.2016.0197
|View full text |Cite
|
Sign up to set email alerts
|

Review of approaches to manage architectural knowledge in Agile Global Software Development

Abstract: Nowadays, Agile and Global Software Development (AGSD) has brought benefits and new challenges to the software industry. Among the main challenges is Architecture Knowledge Management (AKM), due to the following reasons: (i) in Agile Software Development team members prefer to convey knowledge in a face-to-face manner, over transmitting it through formal documents; and (ii) an efficient AKM in Global Software Development involves managing explicit knowledge. These opposite paradigms turn AKM into an unsolved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The main purpose in [4] is architectural KM in Agile and Global Software Development (AGSD). A mapping study was conducted where the authors identified and described approaches to manage architectural knowledge in AGSD teams.…”
Section: Application Of Meta-ethnography Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose in [4] is architectural KM in Agile and Global Software Development (AGSD). A mapping study was conducted where the authors identified and described approaches to manage architectural knowledge in AGSD teams.…”
Section: Application Of Meta-ethnography Methodsmentioning
confidence: 99%
“…This fact leads the researchers to explore strategies of information representation in a leaner and more efficient way, as is the case of [1] and [22]. In KM, one of the main problems is how to [4], [6] represent knowledge so that it is easily shared [26]. Visualization techniques can minimize ambiguity and imprecision in interpreting shared information.…”
Section: (4) Determining How the Studies Are Relatedmentioning
confidence: 99%
“…“A Mechanism to Explore Proactive Knowledge Retention in Open Source Software Communities” is authored by Rashid, Clarke, and O'Connor. Knowledge management and knowledge retention is a classic topic in software organizations and its connection with Open Source Software is very promising. In this paper, authors present a method towards the formation of proactive knowledge retention practices in Open Source Software projects to transform contributor's use of knowledge and engagement into knowledge relevant activities like knowledge sharing and transfer.…”
Section: About the Special Issuementioning
confidence: 99%
“…Several works address AKM in software engineering [28][29][30][31][32] , in GSD [33][34][35][36][37] , and even in ASD [6,38,39] ; however, these works do not cover AGSD environments. We, therefore, conducted a systematic mapping review (reported elsewhere [40] ), in which we identified nine approaches used to manage AK that were grouped into three areas: (1) artifact-based, (2) communication-based, and (3) methodology-based. The artifact-based documentation area refers to the use of software development support (repositories, wikis and groupware) to share AK, auto-generated documentation based on communication analysis (relating to emails and code repositories), and lightweight approaches to register architecture designs and decisions.…”
Section: Architectural Knowledge Management In Agile and Global Software Developmentmentioning
confidence: 99%